2022
DOI: 10.1038/s41598-022-07857-2
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with the first UK covid-19 lockdown and the compounding effects of weather

Abstract: The effectiveness of containment measures has been shown to depend on both epidemiological and sociological mechanisms, most notably compliance with national lockdown rules. Yet, there has been growing discontent with social distancing rules during national lockdowns across several countries, particularly among certain demographic and socio-economic groups. Using a highly granular dataset on compliance of over 105,000 individuals between March and May 2020 in the United Kingdom (UK), we find that compliance wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 20 publications
5
13
0
2
Order By: Relevance
“…The year of 2020 ended with a compliance level of 37.45%. This aligns well with the findings of Ganslmeier et al (2022), where compliance is shown to be modulated both by weather and social patterns; compliance dips in the typically hotter months and known periods of socialisation.…”
Section: Effects Of Covid and Policy Responses On Mobilitysupporting
confidence: 89%
See 1 more Smart Citation
“…The year of 2020 ended with a compliance level of 37.45%. This aligns well with the findings of Ganslmeier et al (2022), where compliance is shown to be modulated both by weather and social patterns; compliance dips in the typically hotter months and known periods of socialisation.…”
Section: Effects Of Covid and Policy Responses On Mobilitysupporting
confidence: 89%
“…The factors influencing compliance are many and of course vary from one person to the next. For example, Ganslmeier et al (2022), in a UK study, highlighted increased symptoms of fatigue based among males, the divorced, part-time employees, and/or parents of more than two children during periods of warmer temperature. By considering a number of variables, we can, however, offer some insights about how populations respond in aggregate.…”
Section: Effects Of Covid and Policy Responses On Mobilitymentioning
confidence: 99%
“…The second similarity relates to the extent of partisan polarization in the US, which has also been widely documented in the UK 11,25 . Debates have focused on whether distinct voter groups have systematically different attitudes, behaviours, and policy priorities, and if so, what can explain these differences 26 . Partisan ideology has notably been argued to shape how people respond to scientific facts 27 .…”
Section: Context and Backgroundmentioning
confidence: 99%
“…8 The right panel suggests that ROLD COMP(p) Pareto-dominates ROLD ACT even for small compliance levels when restricting to moderate values of χ, and Pareto-dominates over all tested χ's for sufficiently large levels of compliance. We also consider a variation of limited compliance in which we allow each age group to have a group-specific compliance fraction calibrated from empirical data (Ganslmeier et al 2022) and the resuls are very similar (Appendix EC.8.4).…”
Section: Dual-targeted Recommendations With Limited Compliancementioning
confidence: 99%
“…For CURFEW, the proposed calculation just replaces a g (t) in these equations with a,eff g The performance of limited compliance policies with age-group-specific compliance, for different compliance levels. We estimate a relative scaling of compliance fractions across age groups using the estimates in Ganslmeier et al (2022). Keeping the relative scaling across age groups fixed, and denoting the compliance fraction for the least compliant age group by p, we look at the performance of ROLD COMP-NH(p) as p varies.…”
Section: Ec83 Time-average Aggregate Activity Levels For Age Groupsmentioning
confidence: 99%